2012
DOI: 10.5430/jbar.v1n1p99
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Communication, Job Stress and Citizenship Behaviour of IT Employees in Nigerian Universities

Abstract: The study examined the relationship among organizational communication, job stress, and citizenship behaviour of IT employees in Nigerian universities and investigated if differences existed in the rating of these variables between federal and state university employees. Data were collected from IT employees in University of Agriculture Makurdi and Benue State University Makurdi (n = 49). Using Pearson correlation coefficient, t-test and regression model as tools of data analysis, the study found that there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The present research will investigate the impact of organizational identification, trust and corporate ethical values (CEV) on OCB. Previous research has investigated the relationship between transformational leadership and OCB (Lin & Hsiao, 2014), organizational commitment, job satisfaction and OCB (Hussain, Ahmad, Ahmed, Saleem & Munir, 2012;Ortiz-Zayas et al, 2014); charismatic leadership, work engagement and OCB (Babcock-Roberson & Strickland, 2010), organizational communication, job stress and OCBs (Ayatse & Ikyanyon, 2012), organizational climate and OCB (Randhawa & Kaur, 2015); however, there have been no empirical work on understanding the roles of organizational identification, trust and ethical corporate values in employee engagement-OCB relationship, either in India or abroad.…”
Section: Introductionmentioning
confidence: 99%
“…The present research will investigate the impact of organizational identification, trust and corporate ethical values (CEV) on OCB. Previous research has investigated the relationship between transformational leadership and OCB (Lin & Hsiao, 2014), organizational commitment, job satisfaction and OCB (Hussain, Ahmad, Ahmed, Saleem & Munir, 2012;Ortiz-Zayas et al, 2014); charismatic leadership, work engagement and OCB (Babcock-Roberson & Strickland, 2010), organizational communication, job stress and OCBs (Ayatse & Ikyanyon, 2012), organizational climate and OCB (Randhawa & Kaur, 2015); however, there have been no empirical work on understanding the roles of organizational identification, trust and ethical corporate values in employee engagement-OCB relationship, either in India or abroad.…”
Section: Introductionmentioning
confidence: 99%
“…Communication can be formal which follows the formal structure of an organization or informal which is based on social relationships (Kandlousi, Ali & Abdollahi, 2010;Guffy, Rhoddes & Rogin, 2005) and can flow in downward, upward and cross-wise directions (Ayatse, 2005). Study by Ayatse and Ikyanyon (2012) provided evidence that organization communication is an important predictor of IT employees in Nigerian universities which implies that employees' citizenship behavior will be increased when they are satisfied with the communication channels and processes in the organization. Another study by Kandlousi, Ali and Abdollahi (2010) supported the findings that a relationship existed between OCB and organizational communication.…”
Section: Organizational Communication and Organizational Citizenship mentioning
confidence: 99%
“…Viewed on the other hand OCB is able to increase the level of employee stress as stated by Jain (2012) in his study found that OCB has a negative and significant effect on work stress. (Ayatse & Ikyanyon, 2012) based on his research in Negeria found different results that OCB had a positive effect on work stress.…”
Section: Introductionmentioning
confidence: 98%